Information skills included in information literacy assessment tools - Dos Santos, Camila Araújo [UNESP]; Casarin, Helen Castro Silva [UNESP] (My University, 2014)
Internationally there are validated instruments that are used on a large scale to verify the information literacy of individuals in different contexts. Their results serve as a diagnostic for the planning and implementation of information literacy activities. In Brazil there is no validated assessment tools of information literacy. An analysis of contents of four international instruments attached to the upper level educational institutions duly recognized in the literature of the field and validated. The results will be presented related to information literacy addressed in these instruments. It was found that the instruments analyzed the skills focused on the identification of terms of the informational needs, the preparation and construction of search strategies available in parameter two of the Association of College and Research Libraries; differentiation of information sources (parameter one); evaluation and selection of informational sources and selection of the theme searched information (parameter three); and, finally, the abilities of the ethical issue related to use of the information (parameter five). The parameter four, which is facing the communication of information, was not addressed by the instruments. It was concluded that there is a concern of those responsible for preparing the instruments covered with more traditional technical aspects of training users and aspects of information literacy at the expense of ethical and aesthetic aspects.
Habilidades informacionais abordadas em instrumentos de avaliação de competência informacional
Keywords: Assessment tools; Information literacy; Information skills